The Speech Act of Complaining in Japanese Anime - Citra, Laras Wibawati; Firmansyah, Dian Bayu; Hamidah, Idah (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2020)
The purpose of this research is to find out the form of speech act of complaint by children character on â€œStand by MeÂ Doraemonâ€Â film and to describe complaint strategy that is used by the children to older people and among children. This research used illocutionary speech acts theory by Searle (1975) and theory of complaint strategies by Trosborg (1995). This research used descriptive qualitative method. The results found 30 data containing complaints by children's character to older people and among children either directly or indirectly. Based on Trosborg classifications, the complaint strategies found in this study can be categorized into four categories, including complaint strategy with no explicit reproach (4 data), complaint strategy with expression of annoyance or disapproval (17 data), complaint strategy with accusation (1 data), and complaint strategy with blaming (8 data). The findings also showed that the children character on this film mainly use complaining strategies with expression of annoyance or disapproval.